Synthesis of 5‐Fluorouridine Nucleolipid Derivatives and Their Cytostatic/Cytotoxic Activities on Human HT‐29 Colon Carcinoma Cells. Issue 12 (December 2013) - Malecki, Edith; Farhat, Anisa; Bonaterra, Gabriel A.; Röthlein, Doris; Wolf, Martin; Schmitt, Jürgen; Kinscherf, Ralf; Rosemeyer, Helmut
Abstract One of the major drawbacks of chemotherapeutics is their insufficient penetration through cell membranes due to a high hydrophobicity. Thus, we have synthesized a series of selected nucleolipid derivatives of 5‐fluorouridine (5‐FUrd; 2a), carrying lipophilic moieties at N(3) and/or in the 2′, 3′‐O‐position (i.e., 3a–7a and 3c), and tested their cytostatic/cytotoxic activities using HT‐29 human colon carcinoma cells, in comparison with, e.g., 5‐FU (1) and 5‐FUrd (2a). Incorporation and intracellular localization of the substances under test were performed after conjugation with the fluorochrome Atto 425. We showed that all 5′‐O‐labelled Atto 425 derivatives were incorporated by the human HT‐29 cells and accumulated in their cytoplasm. Moreover, after 24‐h treatment of HT‐29 human colon carcinoma cells, 1 or 2a (10, 20, 40, or 80 μM) revealed a significant (14–23 or 33–45%, resp.) decrease of the viability in comparison with the (negative) control. Interestingly, derivatives 3a and 3c (40 and 80 μM) led to a significant (77–95 or 89–96%, resp.) inhibition of survival of human HT29 cells, i.e., these two substances were ca. 63–72% or ca. 75%, respectively more effective than 5‐FU (1; positive control). Furthermore, derivative 5a showed a significant, i.e., 30 and 86%, inhibition of the survival at 40 and 80 μM, respectively in comparison with the (negative) control. Some synthesized 5‐FUrd derivatives turned out to be more effective than 5‐FU (1) or 5‐FUrd (2a).